Rational design of original fused-cycle selective inhibitors of tryptophan 2,3-dioxygenase - Kozlova, A; Thabault, L; Liberelle, M; Klaessens, S; Prévost, JRC; Mathieu, C; Pilotte, L; Stroobant, V; Van den Eynde, B; Frédérick, R (American Chemical Society, 2021)
Tryptophan 2,3-dioxygenase (TDO2) is a heme-containing enzyme constitutively expressed at high concentrations in the liver and responsible for l-tryptophan (l-Trp) homeostasis. Expression of TDO2 in cancer cells results in the inhibition of immune-mediated tumor rejection due to an enhancement of l-Trp catabolism via the kynurenine pathway. In the study herein, we disclose a new 6-(1H-indol-3-yl)-benzotriazole scaffold of TDO2 inhibitors developed through rational design, starting from existing inhibitors. Rigidification of the initial scaffold led to the synthesis of stable compounds displaying a nanomolar cellular potency and a better understanding of the structural modulations that can be accommodated inside the active site of hTDO2.